Human Enteric Viruses Detection in Raw and Reclaimed Wastewaters in Two Cities in Southern Italy. (March 2022) - Monini, M.; Ianiro, G.; Delogu, R.; Battistone, A.; Amato, C.; Bartolo, I. DI
Abstract : Purpose: Human enteric viruses are frequently associated with outbreaks or sporadic cases with a wide range of symptoms from mild to acute gastroenteritis, hepatitis, meningitis or paralysis. Most of these viruses are non-enveloped being highly resistant in the environment where may persist for long time. Viruses may be released in the environment through wastewaters causing contamination of crops by irrigation water. The purpose of the study is to assess the presence of human enteric viruses in urban sewages and to evaluate to which extent viruses could be released in the environment through treated wastewater. Methods & Materials: In this study, the presence of human enteric viruses was evaluated in raw and reclaimed wastewaters. During 2015, 146 sewage samples (98 collected at the inlet and 48 at the outlet of the collector sewers) from two Italian cities were tested by real-time reverse transcription-PCRs for norovirus (NoV GI, GII), group A rotavirus (RVA), and hepatitis E virus (HEV). For enteroviruses (EVs) detection, the isolation in cell culture, that enables to distinguish between poliovirus (PV) and non-polio enteroviruses (NPEVs), was followed by RT-PCR and sequencing. Results: NoV was the most prevalently detected in 59% of samples (5.3% inlets of the collector sewers and 45.8% outlets), followed by RVA recorded in 45.9% sewage samples (48% of influent and 41.7% of effluent samples). HEV was only detected in the inlet samples (4.8%). All 61 EV positive samples were typed as NPEVs and were identified in 43.1% of sewage samples (60.2% of influent and 8.3% of effluent samples). Forty-eight influents were initially collected and, 24 hours later, 48 effluents were collected from the same plants. Results showed residual RVA, NoV and EV in 37.5%, 29.2% and 6.3% of the 48 paired samples, respectively. Conclusion: The use of urban sewages for surveillance of human pathogens is promising, allowing the evaluation of viral circulation in adult population independently from subjects' age and disease severity. The presence of enteric viruses in effluents, is a concern since also infectious NEPVs were detected. This finding highlights the need of an effort to reduce the risk of releasing viruses in the environment.